The Interaction Of Feldspar, Mica And Quartz With Different Collectors During Froth Flotation - Ibrahim, Ismail (2012)
Malaysian pegmatite sample containing feldspar, quartz and mica as major minerals were studied. XRF, XRD, ore microscope, FESEM equiped with EDX and AAS were extensively used in the characterization studies. The amount of feldspar in the sample was determined follow the feldspar convention and found that at approximately 61% feldspar (majority is microcline), 27% quartz and 4% mica. FESEM observation found that quartz was interlocked with feldspar in the size range between 10 to 1400 μm required proper liberation before proceed to concentration (flotation. Iron bearing presented as free discrete particle and interlock with quartz and feldspar was removed by magnetic separator.